Efektivitas Audit Intern dalam Pencegahan Fraud pada Pemerintahan Desa di Kabupaten Majalengka - Khoerulloh, Abd. Kholik; Krisniawan, Hendra; Aziz, Holis Abdul (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2024)
Village governments as administrative entities with special autonomy often face the risk of misuse of funds and weaknesses in financial governance. This study aims to examine the effect of internal audit quality and auditor independence of the Majalengka Regency Inspectorate on fraud prevention efforts in the village government environment through internal audit effectiveness as an intervening variable. This research method uses a quantitative approach by collecting data through a survey of a sample of 40 village secretaries which is then analysed with fath analysis techniques. The results show that internal audit quality has a significant positive effect on fraud prevention through internal audit effectiveness with an original sample of 0.390 and P Value 0.003 0.05 and internal auditor independence has a significant positive effect on fraud prevention through internal audit effectiveness with an original sample of 0.280 and P Value 0.045 0.05. This research is expected to make a valuable contribution to related parties, such as the Majalengka Regency Inspectorate, village governments, and other stakeholders in improving financial management practices that are more transparent, accountable, and effective, so as to reduce the risk of fraud in village governments in Majalengka Regency.